Studying Some Important Aspects of Corrugated Steel Web in Girders - Maryam Jumaa (Misan Journal of Engineering Sciences)
As a result of the high advantages of corrugated steel webs, their use has advanced over the conventional plate in recent times. The corrugated web girder has a distinctive geometrical form that enhances the shear buckling behavior of the girder. have a bending and shear behavior different from a conventional plate girder and a higher moment of inertia (I) (secondary axis) than ordinary webs; therefore, corrugated webs provide stiff deflection and rotational motion to the skin in a structure. Corrugated steel webs function similarly to the "accordion effect," especially in the context of bridges. When a bridge is subjected to the weight of vehicles or external forces from the environment, the corrugated steel web can undergo deformation resembling that of an accordion, with expansion and contraction occurring along its corrugated pattern. This behavior is due to the inherent flexibility of the corrugated steel, which allows it to absorb and distribute applied loads more effectively. Although studies are underway to address various aspects such as different loadings or different sections related to their use in civil engineering applications, particularly in bridges. This paper dealt with various aspects of studying corrugated steel webs, including ways to combine them with reinforced concrete to create a composite structure with high resistance and hardness. Severalstudies have also been addressed to develop the efficiency of CSW and improve their behavior, especially to resist shear buckling and improve the behavior of bridges under loads in general, which helps engineers improve the design of bridges to suit developments.